Świadomość konsumencka młodzieży - Barwicka , Agnieszka M. (Studia Edukacyjne, 2020)
Young people face many choices in modern times. The flood of information means that a young person must make many decisions in line with their knowledge and hierarchy of values. Since the development of media and technology has become very important in the everyday life of average teenagers, brands presenting their products reach them through all possible avenues. Regardless of whether teenagers want it or not, they have to face the impact of advertising and select content they find useful. The article presents the results and interpretation of the results of own research conducted on youth.